2020
DOI: 10.1259/bjr.20201166
|View full text |Cite
|
Sign up to set email alerts
|

Clumped vs non-clumped internal enhancement patterns in linear non-mass enhancement on breast MRI

Abstract: Objective: To compare positive predictive values (PPVs) of clumped vs non-clumped (homogenous and heterogeneous) internal enhancement on MRI detected linear non-mass enhancement (NME) on MRI-guided vacuum-assisted breast biopsy (MRI-VABB). Methods: With IRB (Institutional Review Board) approval, we retrospectively reviewed 598 lesions undergoing MRI-VABB from January 2015 to April 2018 that showed linear NME. We reviewed the electronic medical records for MRI-VABB pathology, any subsequent surgery and clinical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…We also excluded patients when the NME features were described as associated findings, which explains the PPV difference from other studies that included NME as primary and associated findings. [25][26][27] Our results show the features of the breast NME lesions in asymptomatic patients referred for screening MRI. We observed the high potential risk for malignancy in the clustered-ring enhancement, followed by the clumped pattern.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…We also excluded patients when the NME features were described as associated findings, which explains the PPV difference from other studies that included NME as primary and associated findings. [25][26][27] Our results show the features of the breast NME lesions in asymptomatic patients referred for screening MRI. We observed the high potential risk for malignancy in the clustered-ring enhancement, followed by the clumped pattern.…”
Section: Discussionmentioning
confidence: 53%
“…We also excluded patients when the NME features were described as associated findings, which explains the PPV difference from other studies that included NME as primary and associated findings. 25 - 27 …”
Section: Discussionmentioning
confidence: 99%
“…Chen et al examined 120 cases of linear enhancement and reported a PPV of 20.8%, with no significant difference due to internal enhancement or size difference [ 14 ]. The 2003 edition of BI-RADS-MRI used the term “ductal” to refer to intraductal lesions, but the 2013 edition no longer uses this term.…”
Section: Introductionmentioning
confidence: 99%
“…The histological type of NMEs is listed as focal adenosis, fibro-cystic, radial scar, complex sclerosing lesion, inflammatory changes, intraductal papilloma, flat epithelial atypia, lobular carcinoma, diffuse invasive breast cancer, invasive ductal carcinoma, and DCIS [ 38 41 ].…”
Section: Introductionmentioning
confidence: 99%
“…NME is noted as the primary lesion in about 20% of cases, of which 20.8% are malignant and 84% are noninvasive ductal carcinoma of the breast [ 41 , 42 ]. On the other hand, DCIS is often noted as a lesion with calcification on MG, and DCIS with a high histological grade, such as those with necrosis, are characterized by characteristic non-mass images on MRI findings, which are highly suspicious of malignancy [ 43 49 ].…”
Section: Introductionmentioning
confidence: 99%